Correction: Loss of β-Glucocerebrosidase Activity Does Not Affect Alpha-Synuclein Levels or Lysosomal Function in Neuronal Cells. - Georgia Dermentzaki (PLoS ONE, 2021)
[This corrects the article DOI: 10.1371/journal.pone.0060674.].